Graduate employability - Abdul Rahman, Shukran (2015)
The global trend of the world of work is shaped by disruptive technologies such as advanced robotics, the Internet of Things, and the automation of knowledge work. HE is to prepare talents to function well in the society that is very much influenced by the global trends. This presentation discusses the objectives of HE, the key learning areas, the quality of graduates, and their employment. It also outlines recommendation to enhance graduate employability